OPTIMASI FORMULA SEDIAAN KRIM EKSTRAK ETANOL 95% DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) - Dyera Forestryana; Yuliani; Aristha Novyra Putri (BORNEO JOURNAL OF PHARMASCIENTECH, 2020)
Pandan wangi leaves (Pandanus amaryllifolius Roxb) contain chemical compounds of flavonoids, alkaloids, polyphenols, saponins, and essential oils that have medicinal properties. The aims of this study are to determine the optimum cream formula from pandan wangi extract based on physical characteristics included organoleptic, homogeneity, pH, spreadability, adhesion, viscosity, and type of cream. Pandan wangi leaves were extracted by maceration method using 95% ethanol, then made five formulas with a base ratio of stearic acid and Cera alba, namely F1 (5%:15%), F2 (10%:10%), F3 (10%:20 %), F4 (15%: 5%), and F5 (20%: 10%). The homogeneity test showed that all formulas has good homogeneity, the pH test results were 5.5-6.4, the spreadability ranged from 1.32-28.21 cm g / sec, the adhesion ranged from 3.21-45.92 seconds, the results of the viscosity were 4280-19366 Cps and the type of cream was the M / A. The results of the physical characteristics of the five formulas showed that the pandan wangi leaves cream met the requirements for good topical preparation. The results of the study based on the adhesion, spreadability, and viscosity test showed that the optimum formula obtained at F3 with a concentration of 10%: 20% that fulfilled the physical quality test.